Combinatoire collocationnelle et linguistique de corpus dans l’apprentissage lexical du FLE - Kazlauskienė, Vitalija (2023)
The importance of stereotypical uses of language, especially in the area of collocational combinatorics, is decisive in language teaching and learning. This type of lexical relationship is difficult for non-native learners to acquire because of its complexity, not only in terms of lexical use, but also in terms of particular linguistic awareness. Learners’ collective corpora can be revealing in describing their transitional competence. The diagnostic of interlanguage-specific difficulties makes it possible to evaluate the progression of a target language, to describe it, to identify its hegemonic variety and to create the most effective activities. In this article, we will discuss the issue of interlanguage in the learner corpora and language corpora for use in lexical learning in French as a foreign language lessons. We address questions that a learner of L2 French has, which are sometimes difficult to find answers to in scholarly grammars or L2 French workbooks.
Keywords: collocation; lexical competence; L2 French; language corpora; learner’ corpora; interlanguage